Confronting religious violence : Christian humanism and the moral imagination - Wallace, Catherine M. (Confronting Fundamentalism Book., 2016)
Confronting Religious Violence: Christian Humanism and the Moral Imagination tells the tale of Christian theocracy in the West. Who converted whom was never entirely clear: the empire did stop feeding people to the lions for public entertainment; but Christianity was theologically corrupted by its official role in legitimating empire-as-usual. That theological corruption led to crusades, inquisitions, torture, and so forth. And it leaves us with a major question: is God violent? More dangerously yet: is violence our only option in response to wrongdoing? Are we morally obligated to injure thos.